2022
DOI: 10.3390/membranes12050460
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselectivity of Interaction of Nonsteroidal Anti-Inflammatory Drug S-Ketoprofen with L/D-Tryptophan in Phospholipid Membranes

Abstract: The mechanisms of stereoselectivity of the interaction of chiral drugs with active sites of enzymes and cell receptors attract significant attention. The first reason is the difference in therapeutic activity of the enantiomers of the common drugs. Another reason is the interest in the role of chiral inversion of amino acids involved in various peptides in the development of many diseases including Alzheimer’s, Parkinson’s, type II diabetes, and a number of other pathological conditions. In our study we use el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 65 publications
1
4
0
Order By: Relevance
“…Comparison of the CIDNP effects measured earlier 4,17,58 with those observed in this work showed that in different media (acetonitrile, water-acetonitrile mixture, aqueous solutions at different pH, and lipid membranes), the same short-lived paramagnetic particles are formed. They are benzyl, ketyl, CO 2 H free radicals and solvated electron.…”
Section: Kp Photolysis With Glycyrrhizic Acid In Different Water-orga...supporting
confidence: 63%
“…Comparison of the CIDNP effects measured earlier 4,17,58 with those observed in this work showed that in different media (acetonitrile, water-acetonitrile mixture, aqueous solutions at different pH, and lipid membranes), the same short-lived paramagnetic particles are formed. They are benzyl, ketyl, CO 2 H free radicals and solvated electron.…”
Section: Kp Photolysis With Glycyrrhizic Acid In Different Water-orga...supporting
confidence: 63%
“…This may have negative effects on many plant species as animal manure and purified wastewater are often used as fertilizers and for irrigation in agriculture ( Gros et al, 2019 ; Papaioannou et al, 2020 ; Ben Mordechay et al, 2021 ; Kesari et al, 2021 ; Li et al, 2022 ). The detrimental effects of KTP on plants can be attributed to its ability to permeate the phospholipid layer of cell membranes and selectively bind to membrane proteins ( Mastova et al, 2022 ). This interaction between KTP and membrane proteins can disrupt their normal functioning.…”
Section: Ecotoxic Effects Of Ketoprofenmentioning
confidence: 99%
“…It binds to the Sudlow II site of albumin, which contains the amino acids leucine, isoleucine, alanine, asparagine, phenylalanine, glycine, cysteine, tyrosine, arginine, lysine and serine [25] . Nevertheless, in this case of free amino acids, interaction of ketoprofen could be expected for the tryptophan, valine and leucine [26,27] . The used media (EMEM, DMEM, RPMI) contain these amino acids (Table S3), so it can be assumed that ketoprofen dissolved in media also occurred there mainly in bound form.…”
Section: Discussionmentioning
confidence: 99%
“… [25] Nevertheless, in this case of free amino acids, interaction of ketoprofen could be expected for the tryptophan, valine and leucine. [ 26 , 27 ] The used media (EMEM, DMEM, RPMI) contain these amino acids (Table S3), so it can be assumed that ketoprofen dissolved in media also occurred there mainly in bound form. When calibration solutions of ketoprofen in media were measured (Figure S1), it was visible, that ketoprofen peak was deformed, which proved the assumption that media have some impact on ketoprofen.…”
Section: Discussionmentioning
confidence: 99%